2012
DOI: 10.1037/a0024740
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Well-Being—Post-Traumatic Changes Questionnaire (PWB-PTCQ): Reliability and validity.

Abstract: The Psychological Well-Being Post-Traumatic Changes Questionnaire (PWB-PTCQ) is an 18 item self-report measure to assess perceived changes in psychological well-being following traumatic events. The aim was to test its psychometric properties. Across three samples, evidence is provided for a single factor structure (invariant across clinical and general populations), high internal consistency (␣ Ͼ .87), six month stability, incremental validity over and above existing measures of posttraumatic growth as a pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 53 publications
5
65
0
3
Order By: Relevance
“…It has been suggested that actual growth is represented by a combination of positive and negative effects of trauma, whilst growth that is reported in the absence of negative effects will potentially lead to maladjustment stemming from ineffective coping strategies such as denial or deliberate attempts not to think of the trauma. [12] It could be argued that positive and negative consequences are interwoven and necessary for growth to take place, [13] and it would therefore be informative to measure both positive and negative dimensions of change following trauma, for example with the Psychological Well-BeingPost-Traumatic Changes Questionnaire, [14] which asks respondents to state whether a given positive attribute applies more, less, or the same as before the traumatic event. The PTGI was used in the present study because it is the most commonly used measure in the existing literature on PTG following ABI, but future research would benefit from employing alternative measures that capture broader post-traumatic experiences, including those specific to medical trauma.…”
Section: Other Commentsmentioning
confidence: 99%
“…It has been suggested that actual growth is represented by a combination of positive and negative effects of trauma, whilst growth that is reported in the absence of negative effects will potentially lead to maladjustment stemming from ineffective coping strategies such as denial or deliberate attempts not to think of the trauma. [12] It could be argued that positive and negative consequences are interwoven and necessary for growth to take place, [13] and it would therefore be informative to measure both positive and negative dimensions of change following trauma, for example with the Psychological Well-BeingPost-Traumatic Changes Questionnaire, [14] which asks respondents to state whether a given positive attribute applies more, less, or the same as before the traumatic event. The PTGI was used in the present study because it is the most commonly used measure in the existing literature on PTG following ABI, but future research would benefit from employing alternative measures that capture broader post-traumatic experiences, including those specific to medical trauma.…”
Section: Other Commentsmentioning
confidence: 99%
“…Second, some researchers have conducted longitudinal investigations to examine the relationship between self-perceived PTG and actual change in PTG domains from pre-to post-trauma (as assessed with current standing versions of inventories such as the PTGI). These studies have generally found these two assessments to be either unrelated or modestly correlated (Frazier et al, 2009;Yanez, Stanton, Hoyt, Tennen, & Lechner, 2011;Joseph, et al, 2012). Third, researchers have assessed the level of agreement between participants' self-reported PTG and family members' and friends' reports of the participants' PTG (discussed below).…”
mentioning
confidence: 99%
“…To our knowledge, this is the first study of post-traumatic growth following ABI to include a medical control group, and is further strengthened by the inclusion of both Future studies would also benefit from measuring post-traumatic growth using other types of instruments, such as the Psychological Well-Being -Post-Traumatic Changes Questionnaire (Joseph et al, 2012), which aims to evaluate perceived negative as well as positive changes in psychological wellbeing following trauma. This would facilitate a more comprehensive assessment of growth and its evolution over time, which in turn could inform rehabilitation approaches aimed at fostering PTG and psychological wellbeing post-injury.…”
Section: Discussionmentioning
confidence: 99%